Key Policy Challenges: Social Security for Migrant Workers - Anita Kristina (Yayasan Rumah Peneleh, 2020)
The purpose of this paper is to analyze various key policy approaches to extending social security to migrant workers. This paper reviews thesocial security system for migrant workers. It then attempts to scrutinize policy approach for analysis. This paper explores the impact of national and international policies and also social security agreements. This pertains to potential impact of the ratification of ILO and UN conventions on migrant workers, which ensure basic social and labor protection. The paper offers insight into the issue of some key policy challenges for the future, including improved design of social security.